2018
DOI: 10.1097/mpa.0000000000000959
|View full text |Cite
|
Sign up to set email alerts
|

The Insulin Receptor Is Colocalized With the TRPV1 Nociceptive Ion Channel and Neuropeptides in Pancreatic Spinal and Vagal Primary Sensory Neurons

Abstract: The present findings provide morphological basis for possible functional interactions among the nociceptive ion channel TRPV1, the InsR, and the proinflammatory neuropeptides SP and CGRP expressed by pancreatic DRG and NG neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 33 publications
6
17
1
Order By: Relevance
“…Further, neuropeptides contained in sensory nerves, such as SP and CGRP may modulate inflammatory processes of both the endocrine and exocrine pancreas. Quantitative immunohistochemical findings supported these findings by showing that the majority of pancreatic vagal and spinal DRG neurons express the TRPV1 receptor, the InsR and sensory neuropeptides [25].…”
Section: Contribution Of Trpv1 Receptor-and Insr-expressing Psns To Pmentioning
confidence: 56%
See 4 more Smart Citations
“…Further, neuropeptides contained in sensory nerves, such as SP and CGRP may modulate inflammatory processes of both the endocrine and exocrine pancreas. Quantitative immunohistochemical findings supported these findings by showing that the majority of pancreatic vagal and spinal DRG neurons express the TRPV1 receptor, the InsR and sensory neuropeptides [25].…”
Section: Contribution Of Trpv1 Receptor-and Insr-expressing Psns To Pmentioning
confidence: 56%
“…It has been demonstrated that about 50% of DRG and nodose ganglia (NG) neurons innervating the rat pancreas express the InsR [25]. It has also been shown that up to 50% of InsR-expressing pancreatic spinal and vagal PSNs exhibit TRPV1 receptor immunoreactivity [25]. Further, about 30% of InsR-expressing pancreatic spinal and vagal sensory neurons contain SP.…”
Section: Neurochemical Characterization Of Somatic and Visceral Psns mentioning
confidence: 99%
See 3 more Smart Citations